Influence of HLA-C Expression Level on HIV Control - Apps, Richard; Qi, Ying; Carlson, Jonathan M.; Chen, Haoyan; Gao, Xiaojiang; Thomas, Rasmi; Yuki, Yuko; Prete, Greg Q. Del; Goulder, Philip; Brumme, Zabrina L.; Brumme, Chanson J.; John, Mina; et al. (Science, 2013)
HLA-C expression and HIV immune control In collaboration with Mary Carrington's group, we showed in Science that the quantity of HLA-C surface protein correlates with HIV disease progression, the probability than HLA-C epitopes will be targeted by the immune system, and the probability that HIV will escape within those epitopes. Mary further showed that HLA-C expression levels are linked to some auto-immune diseases. This is an important study that highlights the the role of HLA-C (which is generally ignored in the field) and demonstrates how our models of selection can be used to generate and test hypotheses. As always, this was a hugely collaborative effort, making key use of data from Philip Goulder, Zabrina Brumme and many others. The MSR Connections team wrote a blog post providing a nice high-level description. Abstract A variant upstream of human leukocyte antigen C (HLA-C) shows the most significant genome-wide effect on HIV control in European Americans and is also associated with the level of HLA-C expression. We characterized the differential cell surface expression levels of all common HLA-C allotypes and tested directly for effects of HLA-C expression on outcomes of HIV infection in 5243 individuals. Increasing HLA-C expression was associated with protection against multiple outcomes independently of individual HLA allelic effects in both African and European Americans, regardless of their distinct HLA-C frequencies and linkage relationships with HLA-B and HLA-A. Higher HLA-C expression was correlated with increased likelihood of cytotoxic T lymphocyte responses and frequency of viral escape mutation. In contrast, high HLA-C expression had a deleterious effect in Crohn’s disease, suggesting a broader influence of HLA expression levels in human disease.